Aurantii Fructus Immaturus enhances natural killer cytolytic activity and anticancer efficacy in vitro and in vivo - Park, Arum; Yang, Yunjeong; Lee, Yunhee; Jung, Haiyoung; Kim, Tae-Don; Noh, Ji-Yoon; Lee, Seungjin; Yoon, Suk Ran (Frontiers in Medicine, 2022)
Aurantii Fructus Immaturus (AFI), extensively used in traditional herbal medicine, is known to have diverse physiological effects against various diseases, including obesity, diabetes, and cardiovascular disease. However, the effects of AFI on the immune system, especially natural killer (NK) cells, remain largely unknown. We aimed to investigate the effect of AFI on NK cell activity in vitro and in vivo and to elucidate the underlying mechanisms. Further, we verified the anticancer efficacy of AFI in a mouse lung metastasis model, underscoring the therapeutic potential of AFI in cancer therapy. Our results revealed that AFI significantly enhanced the cytolytic activity of NK cells in a dose-dependent manner, accompanied by an increase in the expression of NK cell-activating receptors, especially NKp30 and NKp46. AFI treatment also increased the expression of cytolytic granules, including granzyme B and perforin. Furthermore, the expression of CD107a, a degranulation marker, was increased upon treatment with AFI. A signaling study using western blot analysis demonstrated that the phosphorylation of extracellular signal-regulated kinase (ERK) was involved in increasing the NK cell activity following AFI treatment. In the in vivo study performed in mice, oral administration of AFI markedly enhanced the cytotoxic activity of spleen mononuclear cells against YAC-1 cells, which was accompanied by NKp46 upregulation. In addition, we confirmed that cancer metastasis was inhibited in a mouse cancer metastasis model, established using the mouse melanoma B16F10 cell line, by the administration of AFI in vivo. Collectively, these results indicate that AFI enhances NK cell-mediated cytotoxicity in vitro and in vivo via activation of the ERK signaling pathway and suggest that AFI could be a potential supplement for cancer immunotherapy.